Inflammation-dependent oxidative stress metabolites as a hallmark of amyotrophic lateral sclerosis - Luyang Xiong; Michael McCoy﻿; Hitoshi Komuro; Xiaoxia Z. West; Valentin P. Yakubenko; Detao Gao; Tejasvi Dudiki; Amanda Milo; Jacqueline Chen; Eugene A. Podrez; Bruce D. Trapp; Tatiana V. Byzova (2021)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease, with poor prognosis and no cure. Substantial evidence implicates inflammation and associated oxidative stress as a potential mechanism for ALS, especially in patients carrying the SOD1 mutation and, therefore, lacking anti-oxidant defense. The brain is particularly vulnerable to oxidation due to the abundance of polyunsaturated fatty acids, such as docosahexaenoic acid (DHA), which can give rise to several oxidized metabolites. Accumulation of a DHA peroxidation product, CarboxyEthylPyrrole (CEP) is dependent on activated inflammatory cells and myeloperoxidase (MPO), and thus marks areas of inflammation-associated oxidative stress. At the same time, generation of an alternative inactive DHA peroxidation product, ethylpyrrole, does not require cell activation and MPO activity. While absent in normal brain tissues, CEP is accumulated in the central nervous system (CNS) of ALS patients, reaching particularly high levels in individuals carrying a SOD1 mutation. ALS brains are characterized by high levels of MPO and lowered anti-oxidant activity (due to the SOD1 mutation), thereby aiding CEP generation and accumulation. Due to DHA oxidation within the membranes, CEP marks cells with the highest oxidative damage. In all ALS cases CEP is present in nearly all astrocytes and microglia, however, only in individuals carrying a SOD1 mutation CEP marks >90% of neurons, thereby emphasizing an importance of CEP accumulation as a potential hallmark of oxidative damage in neurodegenerative diseases.